2018
DOI: 10.1002/ajmg.a.40496
|View full text |Cite
|
Sign up to set email alerts
|

A rare male patient with Fontaine progeroid syndrome caused by p.R217H de novo mutation in SLC25A24

Abstract: We report the clinical and genetic findings in a 15‐year‐old Spanish boy presenting prenatal and postnatal growth retardation, reduced subcutaneous adipose tissue, premature skin wrinkling, sparse hair, short distal phalanges with small nails, umbilical hernia, wide anterior fontanel, and normal cognitive and motor development. Exome sequencing uncovered a heterozygous mutation in SLC25A24 (NM_013386: c.650G>A: p.R217H) that encodes for the calcium‐binding mitochondrial carrier protein SCaMC‐1. This gain‐of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 15 publications
0
19
0
Order By: Relevance
“…Segmental progeroid syndromes, defined as syndromes with signs of premature aging affecting more than one tissue or organ (Martin 1978), are highly heterogenous genetic disorders. Studies utilizing next-generation sequencing (NGS) approaches have revealed several novel progeroid genes in recent years (Ehmke et al 2017;Jay et al 2016;Lessel et al 2014bLessel et al , 2017bLessel et al , 2018Marbach et al 2019;Paolacci et al 2018;Puente et al 2011;Schrauwen et al 2015;Wambach et al 2018), and broadened the spectrum of phenotypes of many known progeroid conditions and the number of associated genetic causes (Lessel et al 2014a(Lessel et al , 2015Rodriguez-Garcia et al 2018;Soria-Valles et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Segmental progeroid syndromes, defined as syndromes with signs of premature aging affecting more than one tissue or organ (Martin 1978), are highly heterogenous genetic disorders. Studies utilizing next-generation sequencing (NGS) approaches have revealed several novel progeroid genes in recent years (Ehmke et al 2017;Jay et al 2016;Lessel et al 2014bLessel et al , 2017bLessel et al , 2018Marbach et al 2019;Paolacci et al 2018;Puente et al 2011;Schrauwen et al 2015;Wambach et al 2018), and broadened the spectrum of phenotypes of many known progeroid conditions and the number of associated genetic causes (Lessel et al 2014a(Lessel et al , 2015Rodriguez-Garcia et al 2018;Soria-Valles et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…For example, SLC25A24 encodes a carrier protein that mediates electroneutral exchange of Mg-ATP or Mg-ADP against phosphate ions, is responsible for low fat mass in humans and mice (Urano et al, 2015), and is also related with bovine embryonic mortality (Killeen et al, 2016). Mutations in SLC25A24 have been found to be associated with fontaine progeroid syndrome in humans (Rodríguez-García et al, 2018). Furthermore, STXBP3 (also known as Munc18c), involved in insulin-regulated GLUT4 trafficking, has been found to be positively associated with body weight in Large White and Tongcheng pigs (Li et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…The exchange is essential for normal energy production, the metabolism of various molecules, and protein production within cells. SLC25A24 is involved in carcinogenesis (18) and the Fontaine progeroid syndrome (19).…”
Section: Discussionmentioning
confidence: 99%